2012
DOI: 10.1136/thoraxjnl-2012-202678.269
|View full text |Cite
|
Sign up to set email alerts
|

P208 Impact of Morning Symptoms Experienced by COPD Patients on Exacerbation Risk, Rescue Inhaler Usage and Normal Daily Activities

Abstract: Poster sessionsThere was a significant association between inhaler satisfaction and compliance (χ 2 − df=89.7; p<0.001). Other factors related to greater compliance, though to a lesser degree, were fewer maintenance drugs (χ 2 − df=17.7; p<0.001) and male gender (χ 2 − df=2.9; p<0.05). Severity of breathlessness, age and ethnicity were not significantly associated with compliance (p>0.05). Higher compliance scores were significantly associated with better health outcomes (Table). There was also a direct associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
0
4
0
3
Order By: Relevance
“…In COPD patients, cough frequency is highest in the morning, especially in those patients with severe disease (37,38). In addition, early-morning cough can also be used to predict exacerbation risk, rescue inhaler usage and response, ability to carryout normal daily activities, and overall health-related quality of life (39)(40)(41). Thus, smoke-exposed ferrets serve as an effective laboratory tool to evaluate pathogenic events leading up to chronic cough, elucidate mechanisms, and test emerging interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In COPD patients, cough frequency is highest in the morning, especially in those patients with severe disease (37,38). In addition, early-morning cough can also be used to predict exacerbation risk, rescue inhaler usage and response, ability to carryout normal daily activities, and overall health-related quality of life (39)(40)(41). Thus, smoke-exposed ferrets serve as an effective laboratory tool to evaluate pathogenic events leading up to chronic cough, elucidate mechanisms, and test emerging interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Although symptoms can be experienced throughout the day, there is a growing body of evidence that those occurring in the morning may be more severe with the consequent impact on patients' ability to perform tasks 1,5,6 . Moreover, one of these papers suggested that symptoms occurring in the morning may be associated with an increased frequency of exacerbations 6 .…”
Section: Introductionmentioning
confidence: 99%
“…отмечавших по утрам такие симптомы, как кашель и чрезмерное отделение мокроты, по сравнению с пациентами без утренних симптомов отмечалась более высокая частота обострений за последние 12 мес., а также более частое использование препа ратов, облегчающих симптомы в течение дня [5].…”
Section: Discussionunclassified
“…Установлена прямая зависимость между числом обострений ХОБЛ и утренними симп томами [5]. В исследовании показано, что у больных,…”
Section: пульмонология 2016; 26 (1): 65-72unclassified